Interrelationships Between Total Productive Maintenance, Jidoka and Economic Sustainability: Empirical Validation of an Integrated Conceptual Model - García Alcaraz , Jorge Luis (2025)
This study develops and empirically validates an integrated conceptual model that investigates the causal relationships among Total Productive Maintenance (TPM), Jidoka, and economic sustainability (ECSU) within the manufacturing industry. Based on Resource and Capability Theory as well as Systems Theory, the model posits that TPM directly influences both jidoka and ECSU, while jidoka acts as a mediator in the relationship between TPM and ECSU. Utilizing structural equation modeling (SEM-PLS) and data collected from 357 surveys of the maquiladora industry in Ciudad Juárez, Mexico, the analysis confirms that TPM positively affects jidoka (β=,632, p<0,001) and ECSU (β=0,340, p<0,001). Furthermore, jidoka contributes significantly to ECSU (β=0,358, p<0,001) and mediates the effect of TPM on ECSU (β=0,226), resulting in an increased total effect of β=0,566. The researchers conducted graphical analyses that demonstrate nonlinear patterns in relationships. These findings underscore the synergies between TPM and jidoka, which work together to maximize sustainable economic benefits in lean manufacturing environments.